Formate‐Mediated Cross‐Electrophile Reductive Coupling of Aryl Iodides and Bromopyridines. Issue 5 (15th October 2020) - Schwartz, Leyah A.; Spielmann, Kim; Swyka, Robert A.; Xiang, Ming; Krische, Michael J.
Abstract: Two catalytic systems for the formate‐mediated cross‐electrophile reductive coupling of aryl iodides with 6‐bromopyridines are described. Using homogenous rhodium or heterogeneous palladium catalysts, the products of reductive biaryl cross‐coupling could be formed in moderate yield with excellent levels of chemoselectivity. Abstract :